Association between serum zinc levels and recurrent aphthous stomatitis: a meta-analysis with trial sequential analysis - Al-Maweri, Sadeq A.; Halboub, Esam; Al-Sharani, Hesham Mohammed; Shamala, Anas; Al-Kamel, Ahlam; Al-Wesabi, Mohammed Al; Albashari, Abdullkhaleg; Al-Sharani, Amani; Abdulrab, Saleem (Springer Nature, 2021)
Objectives The present meta-analysis sought to investigate the potential association between zinc levels and recurrent aphthous stomatitis (RAS). Methods A comprehensive search of online databases (PubMed, Scopus, Web of Science, and China National Knowledge Infrastructure (CNKI)) was conducted to identify all English and Chinese studies published up to August 2020. All case-control studies that assessed plasma/serum zinc levels were eligible for inclusion. Data were analyzed using Comprehensive Meta-Analysis software version 2.2.046 (Biostat, Englewood, NJ, USA). Trial sequential analysis (TSA) was conducted with the trial sequential analysis program. Results Nineteen case-control studies, involving 1079 RAS cases and 965 controls, were included in the meta-analysis. The pooled results of 19 studies showed that zinc level was significantly lower in RAS patients than in healthy controls (weighted difference in means = ? 21.092, 95% CI ? 26.695 to ? 15.490, I2 = 95.375%, P < 0.001). Upon subgroup analysis by geographic distribution of the sample (Chinese vs. others), the association remained significant in each individual subgroup, although the association was more pronounced among Chinese populations. TSA indicated that the current studies surpassed the required information size, confirming that the differences were reliable. Conclusion The results suggest a significant association between low serum zinc levels and the occurrence of RAS. Although TSA confirmed a solid conclusion, conducting large-scale studies with the highest standards of quality is encouraged. Clinical relevance Determining zinc levels should be considered in diagnosis, management, and prevention of RAS.